2002
DOI: 10.1007/s00464-001-9166-7
|View full text |Cite
|
Sign up to set email alerts
|

The European Association for Endoscopic Surgery clinical practice guideline on the pneumoperitoneum for laparoscopic surgery

Abstract: Preoperatively, all patients should be assessed for the presence of cardiac, pulmonary, hepatic, renal, or vascular comorbidity. Presupposing appropriate perioperative measures and surgical technique, there is no reason to contraindicate pneumoperitoneum in patients with peritonitis or intraabdominal malignancy. During laparoscopy, monitoring of end tidal CO2 concentration is mandatory. The available data on closed- (Veress needle) and open-access techniques do not allow us to principally favor the use of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
375
0
46

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 560 publications
(429 citation statements)
references
References 123 publications
(206 reference statements)
8
375
0
46
Order By: Relevance
“…In addition, the pediatric aspects of some of these diseases were addressed. The Cologne Group was asked to organize a CDC, according to previously established methodology [86]. For this purpose, the methods of a systematic review and a CDC were combined.…”
Section: Selection Of Topicsmentioning
confidence: 99%
“…In addition, the pediatric aspects of some of these diseases were addressed. The Cologne Group was asked to organize a CDC, according to previously established methodology [86]. For this purpose, the methods of a systematic review and a CDC were combined.…”
Section: Selection Of Topicsmentioning
confidence: 99%
“…Most of the studies addressing cardiovascular effects of CO 2 pneumoperitoneum have been performed in healthy subjects, who seem to tolerate pneumoperitoneum without untoward problem [14,15,20]. Similar issues have not been studied under the setting of randomized trial in patients with cardiac co-morbidities [21]. May be hence, there is considerable reticence among surgeons in performing laparoscopy in patients with compromised heart.…”
Section: Discussionmentioning
confidence: 99%
“…Some study define 'normal' insufflation pressure as 12-15 mmHg and a 'low' pressure as 5-7 mmHg [21] while a recent review arbitrarily considered anything less than 12 mmHg as low pressure [33]. Studies in healthy individuals have shown less pronounced decrease in cardiac index using low pressure peritoneal insufflation, while the pulmonary parameters have remained more or less similar in both the groups [13,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most surgical laparoscopic stress is related to CO 2 pressure. 20 A major limitation of the current technique is related to our inability to safely close the gastrotomy. In fact, a critical element of any transgastric procedure is the ability to securely close the gastrotomy site that is required for endoscope passage and specimen removal.…”
Section: Discussionmentioning
confidence: 99%